2004
DOI: 10.1002/mus.20240
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological signs of permanent axonal loss in a follow-up study of patients with Guillain-Barré syndrome

Abstract: The neurophysiological mechanisms for persisting impairment of motor function after Guillain-Barre syndrome (GBS) were assessed in 37 unselected patients 1-13 years after diagnosis. For evaluation of reinnervation and axonal loss, macroelectromyography (macro-EMG) including measurement of fiber density (FD) was performed. Data from neuropathy symptom score, neuropathy disability score, nerve conduction studies, and quantitative sensory examination were ranked and summed to a neuropathy rank sum score (NRSS). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…In our homogeneous group of AIDP patients, a few, most borderline, abnormal values were found. Most patients showed remarkably good recovery in motor and sensory NC, which was at least in accordance with previous findings [5,10,19].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our homogeneous group of AIDP patients, a few, most borderline, abnormal values were found. Most patients showed remarkably good recovery in motor and sensory NC, which was at least in accordance with previous findings [5,10,19].…”
Section: Discussionsupporting
confidence: 90%
“…Persisting signs of demyelination in our neurologically relatively well-recovered AIDP patients could have led to complaints of fatigue, and the aim of this study was to elucidate its possible underlying mechanisms. It was recently shown that impaired muscle strength of ankle dorsiflexion in GBS during long-term follow-up correlates with axonal damage, and that insufficient functional compensatory reinnervation is found more frequently than persisting signs of demyelination [5]. The relation between residual muscle weakness or axonal damage and complaints of fatigue, however, have not been studied before.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, because of the evolving nature of nerve damage and possible secondary pathological changes, e.g. secondary axonal damage in AIDP [7,8] or because of critical illness [9], subtype classification can change during the disease course [10]. Furthermore, ganglioside antibodies directed against (para)nodal structures in AMAN can cause conduction failure, which either resolves rapidly or leads to secondary Wallerian-like axonal degeneration.…”
Section: Introductionmentioning
confidence: 99%